Creative Economy-Based Da'wah Approach: in the Deaf Community in Lampung - Mantik, Aliyah; Romli, Khomsahrial; Yanti, Fitri; Fauzi, Fauzi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This study aims to describe the empowerment-based da'wah approach among the deaf in the Lampung region. This research also identifies the elements of persuasive da'wah in the process of the empowerment process. This study used a descriptive qualitative method by collecting data through interviews and observations and searching literature sources that were considered relevant. The results showed that empowerment has two functions, first as an instrument to build economic independence, which is carried out through providing skills based on hobby development. Secondly, empowerment becomes a persuasive da'wah instrument. The process of preaching uses sign language with an orientation to change the dimensions of religiosity, so that there is a change in understanding, experience and appreciation of religion towards a positive direction and an increase in the confidence of members of the deaf community.Penelitian ini bertujuan mendeskripsikan pendekatan dakwah berbasis pemberdayaan pada kalangan tunarungu di wilayah Lampung. Penelitian ini juga sekaligus mengidentifikasi unsur-unsur dakwah persuasif dalam proses pemberdayaan yang dimaksud. Penelitian ini menggunakan metode kualitatif deskriptif dengan mengumpulkan data melalui wawancara dan observasi serta penelusuran sumber pustaka yang dipandang relevan. Hasil penelitian menunjukkan pemberdayaan memiliki dua fungsi: pertama sebagai instrumen membangun kemandirian ekonomi, yang dilakukan melalui pembekalan keterampilan berbasis pengembangan hobi. Kedua pemberdayaan menjadi instrumen dakwah persuasif. Proses dakwah menggunakan bahasa isyarat dengan orientasi perubahan dimensi-dimensi religiusitas, sehingga terjadi perubahan pemahaman, pengalaman dan penghayatan kegamaan kearah positif dan peningkatan rasa percaya diri para anggota komunitas tunarungu.